HELMET USE COMPLIANCE SURVEY FOR CRANIOFACIAL TRAUMA PREVENTION AMONG MOTORCYCLISTS IN JAYAPURA CITY RING ROAD - Bolly, Hendrikus Masang Ban; Trajanus Laurens Yembise (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: This study provides insights on helmet compliance among motorcyclists in Jayapura City to help prevent head injuries. The analysis shows non-compliance with helmets, especially on the Jayapura Ring Road, where up to four people ride a single motorbike. Consequently, accidents causing head injuries result in greater health and humanitarian impacts. Abstract: Introduction:  Compliance with helmet use by motorcycle riders and passengers passing through the highway is one of the important factors in preventing craniofacial injuries and head injury. This study designed to survey and evaluate the compliance with helmet use among motorcyclists and passengers on the ring road in Jayapura City. Methods: This time-based survey study observed compliance with helmet use by motorcycle riders and passengers passing through the Jayapura city ring road for 14 days of observation at three-time orders (morning, afternoon, and evening). Analysis of the collected data was carried out descriptively. Results: The results showed that during the study period, there were 6,411 motorcycles passing through, 18,602 motorcycle passers-by were at moderate risk of injury due to not wearing helmets (MR-IV) and 11,849 were at high risk (HR-II). The peak of non-compliance with helmet use occurred in the afternoon period (T3). The results showed that 71.92% of the HR-V group did not obey helmet use; 184.82% of the HR-II group did not obey helmet use. While non-compliance with helmet use in the MR-IV group even reached 290.15%. Conclusion: Helmet use compliance among motorcycle riders and passengers on the Jayapura Ring Road is low, increasing their risk of head injuries in accidents. This highlights the need for strategies to reduce helmet non-compliance in Jayapura City. The study focuses on one of the busiest routes, and further research is needed to assess helmet compliance on other busy routes in the city for a more comprehensive understanding.